THE INFLUENCE OF MARKETING MIX AND SERVICE QUALITY ON REPURCHASE INTENTION WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT SINGHASARI RESORT – EAST JAVA - Aprelia Rizki Prastika; Putu Nina Madiawati; Mahir Pradana (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the influence of the marketing mix, service quality, and customer satisfaction on repurchase intention at Singhasari Resort. The research employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The sample consists of guests who had stayed at least once at Singhasari Resort during the period of January 2024 to November 2025. The findings indicate that (1) the marketing mix has a significant effect on customer satisfaction and repurchase intention, (2) service quality significantly influences customer satisfaction and repurchase intention, although it represents the weakest predictor, (3) customer satisfaction significantly affects repurchase intention, and (4) customer satisfaction mediates the relationship between the marketing mix and service quality on repurchase intention.